Possibility of using salivary cortisol in elite soccer players for condition evaluation - Nakamura, M.; Nakamura, D.; Ohiwa, N.; Hayakawa, N. (Journal of High Performance Sport, 2019)
[Purpose] The purpose of the present study was to 1) assess the validity of the lateral flow device (LFD), compared with the enzyme immunoassay (EIA) method, for determining salivary cortisol concentrations; and 2) evaluate the saliva cortisol response to training and soccer games. [Method] Sixteen U-22 Japan men`s national soccer players participated in the present study. Sixteen players (20.8 ± 1.0 yrs, 177.3 ± 8.6 cm, 71.9 ± 7.2 kg) participated in training camp A, and 12 players (21.1 ± 0.9 yrs, 177.5 ± 9.3 cm, 72.0 ± 8.1 kg) participated in training camp B. Saliva samples were collected at the time of awakening, after training (training camp A), and after the game (training camp B). Saliva sample cortisol concentrations were analyzed by conventional EIA and LFD and the results of each method were compared. [Results] Salivary cortisol concentrations that were analyzed by LFD showed fluctuations that synchronized with EIA methods in Camp A and Camp B, respectively. A positive correlation was observed between cortisol value obtained by LFD analysis and that by EIA method (r = 0.73, p < 0.0001). No proportional bias was observed. Moreover, the salivary cortisol concentration that was determined by LFD analysis changed according to training load. [Conclusion] The salivary cortisol concentration analysis by LFD was determined to be useful for individual condition evaluation in elite athletes.